PRENATAL DIAGNOSIS OF CONGENITAL HEART DISEASE. THE IMPACT OF FETAL ECHOCARDIOGRAPHY WITHIN THE FIELDS OF PEDIATRIC CARDIOLOGY - Valeriu Popescu; Andrei Zamfirescu (Amaltea Medical Publishing House, 2009)
This article presents advances in the fi eld of fetal echocardigraphy and the signifi cant impact of these within the fi elds of pediatric cardiology, perinatology and neonatology. A prenatal diagnosis of congenital heart disease allows improved counseling of the parents, guides the timing and optimal location of delivery, and allows appropriate planning and consultation between the cardiologist and neonatologist. It also facilitates accurate diagnosis and management of fetal arrhytmias, identifi es potential candidates for in utero cardiac intervention and serves as the imaging guidance technique for these procedures. The goals, indications, advantages, limitations and spectrum of congenital heart disease that can be diagnosed are reviewed.